Corporate Performance in Nigeria: The Effect of Oil Price and Exchange Rate Fluctuations - Omoregie, Osaretin Kayode; Olofin, Sodik Adejonwo (International Journal of Economics and Financial Issues, 2019)
Discussions on the separate effect of oil price and exchange rate fluctuations on economic activity and corporate performance in Nigeria are inconclusive. This study investigates the simultaneous influence of oil price and exchange rate and the impact of the different exchange rate regimes adopted in Nigeria on corporate performance, using the Structural-VAR / Historical Decomposition framework. The literature in these areas is sparse. Result from this study suggests that oil price shocks have negative influence on corporate performance with a very short-term positive influence. Exchange rate shocks have positive impact on corporate performance with an instantaneous negative effect. Also, fixed exchange regimes are associated with a downturn in corporate performance, while flexible regimes are associated with improved corporate performance. This result support diversification and flexible exchange rate policies, while corporate managers should adopt risk-hedging strategies to cushion the adverse combined effect of oil price and exchange rate shocks. Keywords: Corporate Performance, Oil Price, Exchange Rate, SVAR, Historical Decomposition, Nigeria JEL Classifications: F38, G3, Q43 DOI: https://doi.org/10.32479/ijefi.8829